2020
DOI: 10.31234/osf.io/e3fh4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Love in the Time of COVID: Perceived Partner Responsiveness Buffers People from Lower Relationship Quality Associated with COVID-Related Stressors

Abstract: Maintaining a satisfying romantic relationship is vital to overall health and well-being, yet relationship quality might be hampered by stressors brought on by the recent Covid-19 pandemic. In the Love in the Time of Covid study, we examine whether Covid-related stressors (i.e., social isolation, financial strain, and stress) are associated with lower relationship quality and greater conflict in relationships, and test whether perceived partner responsiveness—the extent to which people believe their partner un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
142
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(163 citation statements)
references
References 54 publications
(73 reference statements)
17
142
0
Order By: Relevance
“…These findings support our hypothesis and are aligned with past research. Indeed, people in social confinement tend to experience more negative outcomes in their lives (Balzarini et al, 2020;Cellini et al, 2020;Cocci et al, 2020;Lehmiller et al, 2020;Li et al, 2020;Qiu et al, 2020). Against our hypothesis, we also found that most participants indicated increased willingness to have sex since the COVID-19 outbreak.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…These findings support our hypothesis and are aligned with past research. Indeed, people in social confinement tend to experience more negative outcomes in their lives (Balzarini et al, 2020;Cellini et al, 2020;Cocci et al, 2020;Lehmiller et al, 2020;Li et al, 2020;Qiu et al, 2020). Against our hypothesis, we also found that most participants indicated increased willingness to have sex since the COVID-19 outbreak.…”
Section: Discussionsupporting
confidence: 54%
“…This was consistent for both groups, suggesting that using pornography together may have help people to become closer to their partners. If so, this behavior might be a way for single and partnered people to increase social connectedness with others, which has been argued an important predictor of quality of life and well-being (Holt-Lunstad et al, 2010), namely during the pandemic (Balzarini et al, 2020;Okabe-Miyamoto et al, 2020;Vowels, 2020). In contrast, participants with more solitary online pornography use also experienced less sex quality and less satisfaction and intimacy with their partners, which in turn was associated with worse perceived physical health and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations